2016
DOI: 10.1186/s12884-016-1005-x
|View full text |Cite
|
Sign up to set email alerts
|

Could the erythrocyte indices or serum ferritin predict the therapeutic response to a trial with oral iron during pregnancy? Results from the Accuracy study for Maternal Anaemia diagnosis (AMA)

Abstract: BackgroundTreatment of maternal iron-deficiency anaemia can reduce risks of prematurity and low birth weight; hence a reliable diagnosis of maternal iron needs is critical. However, erythrocyte indices and serum ferritin have shown a weak correlation with iron status during pregnancy. This study verified the accuracy of those tests to predict the responsiveness to a therapeutic test with oral iron as reference standard for iron deficiency in pregnant women.MethodsA prospective diagnostic study phase 3 was cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Although the MCH retains accuracy and stability between analysers and is somewhat less affected by pre‐analytical variables, it is not specific for iron deficiency. None of these parameters alone is able to predict response to oral iron 10–12 …”
Section: Haemoglobin Concentration and Red Cell Parameters (Hct MCV M...mentioning
confidence: 99%
“…Although the MCH retains accuracy and stability between analysers and is somewhat less affected by pre‐analytical variables, it is not specific for iron deficiency. None of these parameters alone is able to predict response to oral iron 10–12 …”
Section: Haemoglobin Concentration and Red Cell Parameters (Hct MCV M...mentioning
confidence: 99%
“…18.6% ± 5.3, P = 0.965) ( 16 ). Furthermore, RDW failed to predict responsiveness to iron supplementation therapy ( 17 , 18 ). De Sà et al studied RDW values in new-borns of anaemic and non-anaemic women.…”
Section: Discussionmentioning
confidence: 99%
“…Anemia in pregnancy is a major public health problem, especially in developing countries 1,2 . Different studies have shown different prevalence of anemia during pregnancy ranging from 16.6-95.0% [3][4][5][6] .…”
mentioning
confidence: 99%